Institution of Discipline and Responsibility Values in Students Through Learning Activities as an Effort to Form Citizenship Character - Nurul Afifah Azzahra; Rahman Wahid; Budi Hendrawan (CV. Ksatria Siliwangi, 2025)
This study aims to describe the instillation of discipline and responsibility values ​​in children through learning activities as an effort to form citizenship character from an early age at Adz-Dzikro Kindergarten. This study uses a qualitative approach with a descriptive research type. Data collection was carried out through observation, interviews, and documentation to obtain a comprehensive picture of the learning process and character building implemented in the school. The data obtained were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the instillation of discipline values ​​is carried out through habituation of routine activities, such as following class rules, lining up orderly, and adhering to the learning schedule. Meanwhile, the value of responsibility is instilled through giving simple tasks appropriate to the child's development, such as tidying up toys, completing learning activities, and working together in groups. Children showed a tendency to respond positively to these habits, although there were differences in responses between individuals that require ongoing teacher guidance. The conclusion of the study shows that learning activities integrated with the habituation of discipline and responsibility values ​​play an important role in building the foundation of citizenship character in early childhood. Theoretically, these findings reinforce the concept of experience-based character education, while practically, they provide implications for teachers in developing learning that emphasizes consistent character value instillation from an early age.